2018
DOI: 10.1029/2017wr021728
|View full text |Cite
|
Sign up to set email alerts
|

Relative Influence of Landscape Variables and Discharge on Suspended Sediment Yields in Temperate Mountain Catchments

Abstract: Suspended sediment is an important regulator of stream habitat quality but notoriously difficult to predict and regulate. This difficulty arises because of high natural variability in suspended sediment yield in space and time. Here we quantified associations between suspended sediment yields and discharge, watershed setting (i.e., physiography and lithology), and disturbance history for 10 temperate mountain watersheds (8.5–6,242 ha) in the U.S. Pacific Northwest (H.J. Andrews Long‐Term Ecological Research, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…These rates are within the range of suspended sediment yields measured from forested watersheds lacking active glaciers in the Cascade Range of southwestern Washington and northwestern Oregon (Czuba et al, 2011;Wise and O'Connor, 2016;Bywater-Reyes et al, 2018), and is similar to the conclusion of Major et al (2018) that sediment yield from the Green River basin declined to pre-eruption levels within about 5 years. These rates are within the range of suspended sediment yields measured from forested watersheds lacking active glaciers in the Cascade Range of southwestern Washington and northwestern Oregon (Czuba et al, 2011;Wise and O'Connor, 2016;Bywater-Reyes et al, 2018), and is similar to the conclusion of Major et al (2018) that sediment yield from the Green River basin declined to pre-eruption levels within about 5 years.…”
Section: Contribution Of Tephra Erosion To Volcanogenic Sediment Yieldsupporting
confidence: 74%
See 1 more Smart Citation
“…These rates are within the range of suspended sediment yields measured from forested watersheds lacking active glaciers in the Cascade Range of southwestern Washington and northwestern Oregon (Czuba et al, 2011;Wise and O'Connor, 2016;Bywater-Reyes et al, 2018), and is similar to the conclusion of Major et al (2018) that sediment yield from the Green River basin declined to pre-eruption levels within about 5 years. These rates are within the range of suspended sediment yields measured from forested watersheds lacking active glaciers in the Cascade Range of southwestern Washington and northwestern Oregon (Czuba et al, 2011;Wise and O'Connor, 2016;Bywater-Reyes et al, 2018), and is similar to the conclusion of Major et al (2018) that sediment yield from the Green River basin declined to pre-eruption levels within about 5 years.…”
Section: Contribution Of Tephra Erosion To Volcanogenic Sediment Yieldsupporting
confidence: 74%
“…Within about 6 years after the 1980 eruption, the catchmentscale sediment flux dropped into the range of 10-250 t km À2 year À1 (assuming a soil bulk density of 1000 kg m À3 , this is equivalent to hillslope lowering rates of 0.01-0.25 mm year À1 ). These rates are within the range of suspended sediment yields measured from forested watersheds lacking active glaciers in the Cascade Range of southwestern Washington and northwestern Oregon (Czuba et al, 2011;Wise and O'Connor, 2016;Bywater-Reyes et al, 2018), and is similar to the conclusion of Major et al (2018) that sediment yield from the Green River basin declined to pre-eruption levels within about 5 years. By that time, tephra erosion rates were approaching the limits of measurement ( Figure 8A, Table III), suggesting that the contribution of tephra erosion to streams had declined to the background level of the surrounding undisturbed landscape and that the 1980 tephra had entered the sediment supply system driven by fast and slow mass wasting.…”
Section: Contribution Of Tephra Erosion To Volcanogenic Sediment Yieldsupporting
confidence: 72%
“…Knight & Harrison, 2014), which dominate the record for a decade or more thereafter, obscuring any possible long‐term trend. For example, ~60 years of suspended‐sediment records beginning in the 1950s from 10 mountain watersheds in Oregon showed that each catchment's sediment yield varied over three orders of magnitude (10 0 to 10 3 t/km 2 ), with decadal‐scale increases due to a large storm and to forest management, but no long‐term trends (Bywater‐Reyes et al, 2018). Many western U.S. watersheds with sediment‐flux data have a history of logging and associated dirt‐road use, which elevated fluxes for decades (e.g., Madej & Ozaki, 1996; Reid & Dunne, 1984).…”
Section: Observed Changes To Sedimentary and Geomorphic Processes: Anmentioning
confidence: 99%
“…Although many previous studies have documented how forestry affects streamflow and water quality (e.g., Bladon, Segura, Cook, Bywater‐Reyes, & Reiter, ; Bywater‐Reyes, Bladon, & Segura, ; Gomi, Moore, & Hassan, ; Moore, Spittlehouse, & Story, ; Moore & Wondzell, ; Perry & Jones, ), EFN assessments have historically been concerned with regulation and consumptive use of water resources, such as power generation and agriculture, and have neglected to consider the impacts of forestry on the natural flow regime (e.g., Lewis, Hatfield, Chilibeck, & Roberts, ). In the context of EFN, the impacts of forest harvesting on summertime low flows are of particular interest.…”
Section: Introductionmentioning
confidence: 99%